Understanding the Needs of Hand Control Users, Driver Rehabilitation Specialists, and Dealers/Installers. Issue 4 (2nd October 2014) - Lowe, Evan; Drouin, Nathalie; Venhovens, Paul J.; Brooks, Johnell O.
ABSTRACT Understanding unique perspectives from key stakeholder groups involved in the hand control (HC) industry, including driver rehabilitation specialists (DRSs) who train users how to use their HCs, dealers/installers, and users, may become increasingly important in the United States due to increases in elderly, diabetic, and wounded warrior amputee driving populations. In this exploratory study, phone interviews were conducted with 20 DRSs, 20 dealers/installers, and 20 users regarding their perspectives about HC training, maintenance and operation, and design improvements. Results revealed common views and differences in perspectives about whether HC users should receive training and for how long, when and how often users should receive maintenance on their HCs, and what DRSs, dealers/installers, and users would like to see in the future.